Marketing to the new majority : strategies for a diverse world - Burgos, David; Mobolade, Ola. (New York : Palgrave MacMillan, 2011)
'Today, diversity is the default, not the exception.'Minorities' are already the majority in some of the biggest cities in the United States, and demographers predict that the same will be true of the country as a whole before 2050. Yet companies continue to address the'general market' as a separate audience from ethnic consumers, rather than acknowledging that the new mainstream is itself multicultural. In addition, many who do target multicultural audiences still employ ad strategies that rely heavily on stereotypes and fail to resonate with minority communities. Here, David Burgos and Ola Mobolade look at the changed marketplace revealed in the new 2010 Census data, and show marketers how to develop integrated campaigns that effectively reach these culturally diverse consumer populations. Drawing on interviews with industry leaders and Millward Brown's vast database of consumer research, this book will be a roadmap to the opportunities and challenges of marketing to the new mainstream in a way that feels natural, respectful, and inclusive'--
Includes bibliographical references and index.
Keywords: Marketing -- United States; Multiculturalism -- United States; Minorities -- United States